Inverted classroom: construction of playful games for teaching undergraduate Nursing (Research, Society and Development, 2020)
This study has the goal of reporting the experience of creating ludic games as a pedagogical strategy in the epidemiology subject in an undergraduate nursing course in a brazilian southeastern private university. It is an experience report on the reasoned application of said games to Active Methodologies and Bloom's Taxonomy. We tried to align these activities to the actions of a university extension project titled "Classroom without Walls". It was observed that playful games proved to be an important pedagogical tool in higher education as for they stimulate critical reflection by pupils and bring them closer to reality, promoting the development of their autonomy in the learning process. Therefore, it is concluded that the students showed good development and interest in the search for their knowledge, alongside the construction of future nursing professionals' skills and abilities with theoretical-practical association, improving their decision making.